Formation of professional competence of the future teacher of technologies - I. V. Нevko (Kazimierz Wielki University, 2017)
The article analyzes the scientific and pedagogical research. On their basis, the concept of "professional competence" is considered and its own definition of this concept is presented. A model for the formation of the professional competence of the future technology teacher has been developed and justified. The proposed pedagogical model reflects the goals, objectives, principles, content and organization of the learning process, which allow to develop cognitive interest, individual abilities, abilities and professionally important personal qualities of students, to provide individualization of instruction, independence, that is, to contribute to the effective formation of the professional competence of the technology teacher.